Colores rethorici: Réflexions sur la rhétorique de la couleur dans les mosaïques de Rome du xiie siècle - Riccioni, Stefano (Convivium, 2015)
Abstract Using the methodology called epiconography, this study examines the use and meaning of colors in Roman mosaics executed during the twelfth-century Church Reform. The analysis discovers the rhetorical arrangement of visual speech in the mosaics of San Clemente and Santa Maria in Trastevere. Taken from techniques of manuscript preparation, colors served in the mosaics to articulate and add emphasis to the visual narrative. Considering images and inscriptions together, the observer could “read” the mosaics and discern their meanings. This dual process enabled the mosaics’ patrons and promoters belonging to the Reformed Church hierarchy to supervise the artistic program with particular attention to visual messages.